Evaluasi Kekuatan Daya Dukung Pondasi Bored Pile Dengan Struktur Slab On Pile (Studi Kasus Pada Slab On Pile Sta 14+045 Jalan Tol IKN Paket 3a KKT Kariangau-Karang Joang) - Achmad, S.T., M.T, Karmila; Cholick, Baby Febriyana (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2025)
This study aims to evaluate the load-bearing capacity and strength of the bored piles based on their dimensions and soil testing parameters. SOP 1 STA 14+065 is part of the IKN Toll Road Package 3A KKT Kariangau-Karangjoang, which uses pile slabs due to the soft soil conditions along the road's alignment. A PDA test was conducted to assess the load-bearing capacity of bored pile foundations with an 800 mm diameter with varying depths. Samples from Pile Points P4 B 131 and P4 B 152 were selected because they did not meet the minimum PDA target of 419.6 tons, raising concerns about potential settlement or even structural failure.The load analysis and calculations on the slab-on-pile structure were performed manually based on SNI 1725:2016